2012
DOI: 10.1038/aps.2012.57
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics modeling of levetiracetam in Chinese children with epilepsy

Abstract: Aim: To establish a population pharmacokinetics (PPK) model of levetiracetam in Chinese children with epilepsy. Methods: A total of 418 samples from 361 epileptic children in Peking University First Hospital were analyzed. These patients were divided into two groups: the PPK model group (n=311) and the PPK validation group (n=50). Levetiracetam concentrations were determined by HPLC. The PPK model of levetiracetam was established using NONMEM, according to a one-compartment model with firstorder absorption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Previous studies analyzing oral LEV in pediatric children using a nonlinear mixed‐effects model suggested that a plasma LEV concentration after oral LEV was best fitted by the one‐compartment linear model and the important covariate affecting the CL and V were WT and enzyme‐inducing AEDs . A recent PK study of IV LEV in 52 children with epilepsy aged 1 month‐16 years also demonstrated dose‐proportional PK of LEV.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies analyzing oral LEV in pediatric children using a nonlinear mixed‐effects model suggested that a plasma LEV concentration after oral LEV was best fitted by the one‐compartment linear model and the important covariate affecting the CL and V were WT and enzyme‐inducing AEDs . A recent PK study of IV LEV in 52 children with epilepsy aged 1 month‐16 years also demonstrated dose‐proportional PK of LEV.…”
Section: Discussionmentioning
confidence: 99%
“…PPK model of LEV in Chinese children aged 0.5–14 years with epilepsy showed body weight was a significant covariate for LEV clearance24). Sharpe and Haas9) noted the clearance in the neonates was modeled as a simple function of postnatal age.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of each study are summarised in Table 1. Sneck et al [13] enrolled only healthy subjects, Pigeolet et al included both patients and healthy subjects [14], and the other studies were conducted in patients with epilepsy [15][16][17][18][19][20][21][22][23][24][25][26]. Eight of the fourteen studies enrolled paediatric patients [15,17,18,20,21,[24][25][26]; 2 studies were conducted in neonates [18,21], 4 studies in children less than 18 years of age [15,20,25,26], and 2 studies included both children and adults [17,24].…”
Section: Study Characteristicsmentioning
confidence: 99%